Identification of novel and conserved microRNAs in Panax notoginseng roots by high-throughput sequencing. (December 2015) - Wei, Rongchang; Qiu, Deyou; Wilson, Iain; Zhao, Huan; Lu, Shanfa; Miao, Jianhua; Feng, Shixin; Bai, Longhua; Wu, Qinghua; Tu, Dongping; Ma, Xiaojun; Tang, Qi
Abstract Background MicroRNAs (miRNAs) are small, non-coding RNAs that are important regulators of gene expression, and play major roles in plant development and their response to the environment. Root extracts fromPanax notoginseng contain triterpene saponins as their principal bioactive constituent, and demonstrate medicinal properties. To investigate the novel and conserved miRNAs inP. notoginseng, three small RNA libraries constructed from 1-, 2-, and 3-year-old roots in which root saponin levels vary underwent high-throughput sequencing. Methods P. notoginseng roots, purified from 1-, 2-, and 3-year-old roots, were extracted for RNA, respectively. Three small libraries were constructed and subjected to next generation sequencing. Results Sequencing of the three libraries generated 67, 217, 124 clean reads fromP. notoginseng roots. A total of 316 conserved miRNAs (belonging to 67 miRNA families and one unclassified family) and 52 novel miRNAs were identified. MIR156 and MIR166 were the largest miRNA families, while miR156i and miR156g showed the highest abundance of miRNA species. Potential miRNA target genes were predicted and annotated using Cluster of Orthologous Groups, Gene Ontology, and Kyoto Encyclopedia of Genes and Genomes. Comparing these miRNAs between root samples revealed 33 that were differentially expressed between 2- and 1-year-old roots (8 increased, 25 decreased), 27 differentially expressed between 3- and 1-year-old roots (7 increased, 20 decreased), and 29 differentially expressed between 3- and 2-year-old roots (8 increased, 21 decreased). Two significantly differentially expressed miRNAs and four miRNAs predicted to target genes involved in the terpenoid backbone biosynthesis pathway were selected and validated by quantitative reverse transcription PCR. Furthermore, the expression patterns of these six miRNAs were analyzed inP. notoginseng roots, stems, and leaves at different developmental stages. Conclusions This study identified a large number ofP. notoginseng miRNAs and their target genes, functional annotations, and gene expression patterns. It provides the first known miRNA profiles of theP. notoginseng root development cycle.